(untitled) (Central Asian Journal of Medical Sciences, 2025)
Objective: After lifting COVID-19 restrictions, increased spread of Mycoplasma pneumoniae has been observed in both adults and children, with a growing number of cases showing extrapulmonary involvement. We present reports of three cases: pneumonia with infection-related Stevens–Johnson syndrome affecting 7-8% of body surface area and leading to pulmonary obstruction in a child; pneumonia with rash and severe mucositis in an adolescent; and Fuchs syndrome in an adult. We further discuss the pathogenesis of extrapulmonary manifestations, focusing on the role of the CARDS exotoxin and host immune responses.